Assessment of the external validity of the National Comprehensive Cancer Network (NCCN) guidelines for pancreatic ductal adenocarcinoma in a population of older patients aged 70 years and older. Issue 7 (September 2022) - Rodriquenz, Maria Grazia; Negrete-Najar, Juan-Pablo; Sam, Christine; Sehovic, Marina; Extermann, Martine
Abstract: Introduction: Pancreatic ductal adenocarcinoma (PDAC) mainly occurs in older adults. Since randomized clinical trials (RCTs) provide the highest-quality evidence incorporated in NCCN recommendations, the underrepresentation of older patients in RCTs challenges guidelines' external validity and limits the solidity of evidence in this specific population. Materials and Methods: The study aimed to investigate external validity of NCCN guidelines for PDCA and the impact of reference studies eligibility on overall survival (OS) in a real-world older population. We retrieved RCTs supporting NCCN recommendations for management of PDAC and identified ten topics. We matched a cohort of 707 PDAC patients aged ≥70 years from the Moffitt Cancer Center database with eligibility criteria of 96 reference RCTs to check the proportion of patients eligible for at least two RCTs. Eligibility >60% was rated full validity, 30%–60% partial validity and < 30% limited validity. We also performed log-rank test to assessed whether "eligibility" status affects OS, stratifying by age (70–74; 75–79; ≥80). Results and Discussion: We found full validity for neoadjuvant (57/73 patients; 69.86%), locally advanced (28/39; 71.79%) and second line (88/110; 80%) treatment, while lowest validity was found for adjuvant chemotherapy (37/86; 43%). Eligible status was correlated with a significant OS benefit for adjuvant chemoradiation ( p  = 0.002) in all-comers and for first-line polychemotherapy in patients aged ≥80 ( p  = 0.01). Our analysis supports the limitation of guidelines' external validity in older patients, and hints at possible correlations with survival, although no definitive conclusions can be drawn at this stage. Renewing RCT design with broader eligibility criteria might help increase inclusion of older and thus strengthen the evidence.